Dominasi Kekerasan Seksual terhadap Anak Perempuan: Kegagalan Ruang Domestik Sebagai Lingkungan Aman di Jawa Tengah - Indra Kertati (Universitas 17 Agustus 1945 Semarang, Indonesia, 2026)
This study aims to analyze the phenomenon of violence against children in Central Java, focusing on the dominance of sexual violence against girls and the failure of the domestic sphere as a safe environment. This research employs a descriptive qualitative approach using secondary data from SIMFONI-PPA, supported by relevant literature. The findings reveal that cases of violence against children fluctuate but remain consistently high each year. Girls are identified as the most vulnerable group, with a higher proportion of victims compared to boys. Sexual violence emerges as the most dominant form, indicating serious issues related to power relations, gender inequality, and weak social protection systems. Furthermore, the household, which is expected to be a safe space, is in fact the primary location of violence, with perpetrators largely coming from close relationships such as parents, partners, and the surrounding social environment. These findings highlight that violence against children is not merely an individual issue but a structural problem involving social, cultural, and power dynamics. Therefore, comprehensive child protection approaches that are family-based, gender-sensitive, and cross-sectoral are essential to break the cycle of violence sustainably.